An evaluation of the TARGET (Treat Antibiotics Responsibly; Guidance, Education, Tools) Antibiotics Toolkit to improve antimicrobial stewardship in primary care—is it fit for purpose?. (28th December 2017) - Jones, Leah Ffion; Hawking, Meredith K D; Owens, Rebecca; Lecky, Donna; Francis, Nick A; Butler, Chris; Gal, Micaela; McNulty, Cliodna A M
Abstract: Background: The TARGET ( T reat A ntibiotics R esponsibly; G uidance, E ducation, T ools) Antibiotics Toolkit aims to improve antimicrobial prescribing in primary care through guidance, interactive workshops with action planning, patient facing educational and audit materials. Objective: To explore GPs', nurses' and other stakeholders' views of TARGET. Design: Mixed methods. Method: In 2014, 40 UK GP staff and 13 stakeholders participated in interviews or focus groups. We analysed data using a thematic framework and normalization process theory (NPT). Results: Two hundred and sixty-nine workshop participants completed evaluation forms, and 40 GP staff, 4 trainers and 9 relevant stakeholders participated in interviews (29) or focus groups (24). GP staffs were aware of the issues around antimicrobial resistance (AMR) and how it related to their prescribing. Most participants stated that TARGET as a whole was useful. Participants suggested the workshop needed less background on AMR, be centred around clinical cases and allow more action planning time. Participants particularly valued comparison of their practice antibiotic prescribing with others and the TARGET Treating Your Infection leaflet. The leaflet needed greater accessibility via GP computer systems. Due to time, cost, accessibility and competing priorities, many GP staff had not fully utilized all resources, especially the audit and educational materials. Conclusions: We found evidence that the workshop is likely to be more acceptable and engaging if based around clinical scenarios, with less on AMR and more time on action planning. Greater promotion of TARGET, through Clinical Commissioning Group's (CCG's) and professional bodies, may improve uptake. Patient facing resources should be made accessible through computer shortcuts built into general practice software.